Epidemiological profile of HIV-1 infection in pregnant women of state of Mato Grosso do Sul– Brazil - Figueiró-Filho, Ernesto A.; Senefonte, Flávio R.A.; Lopes, Alessandro H.A.; G.S. Júnior, Virgílio; Botelho, Carlos A.; Duarte, Geraldo (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: The HIV-1 infection in pregnant women some times is subdiagnosed due to the asymptomatic and subclinical characteristics of the disease during pregnancy. The knowledge of the local reality and the epidemiological profile of the HIV-1 infection during pregnancy are important in Brazilian populations. Objective: to evaluate the frequency, the epidemiological profile and the association of HIV-1 infection with maternal age in pregnant women submitted to prenatal scree-ning tests in one State of the Central-West region of Brazil. Methods: prospective study of 71 pregnant women with HIV-1 infection diagnostic of 32512 pregnant women submitted to pre-natal screening in the period of November 2002 to October 2003. This prenatal screening included a serologic investigation of 10 infection diseases using the filter paper technique with ELISA methodology. The HIV-1 infection was diagnostic by ELISA method and it was confirmed by Western blot. Thedata were described by media, and some sample data association were performed by chisquared test in contingency tables .It was accepted p<0.05 (95%) to reject the nullity hypotesis. Results: within the 32512 pregnant women submitted to pre-natal screening tests, it was found a frequency of 0.2% (71) of HIV-1 infection, and most of the patients (88.7%) did not know their viral infection by the HIV-1 before pregnancy. The medium dignostic age was 24.4±5.3 years, and the pregnantinfected women provenient from the county regions of the State represented 62% of the sample. There was no statistical significancy between the age and the frequency of HIV-1 infection in the pregnant women studied. Most of the infected pregnant women were in their third pregnancy (31.25%) and the second trimester was the most prevalent period of diagnosis (45.5%). The cesarian section was predominant (82%) with term neonates (89%). There was one miscarriage and one case of fetal death. Conclusion:the HIV-1 infection in pregnant women of a State of the Central-West region of Brazil waslower than the rates found in other brazilian studies whereas was almost equal the international rates. There was not found inthe worldwild literature such a screening as it was performed in the present study. The importance of the earlier prenatal HIV-1 screening must be emphasized once on the present study most of the infected pregnant women were the first timediagnosed during pregnancy within the second trimester and having at least one child previously the HIV-1 diagnosis.